2020
DOI: 10.1038/s41396-020-00822-9
|View full text |Cite
|
Sign up to set email alerts
|

Plant resistome profiling in evolutionary old bog vegetation provides new clues to understand emergence of multi-resistance

Abstract: The expanding antibiotic resistance crisis calls for a more in depth understanding of the importance of antimicrobial resistance genes (ARGs) in pristine environments. We, therefore, studied the microbiome associated with Sphagnum moss forming the main vegetation in undomesticated, evolutionary old bog ecosystems. In our complementary analysis of culture collections, metagenomic data and a fosmid library from different geographic sites in Europe, we identified a low abundant but highly diverse pool of resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 92 publications
5
29
0
1
Order By: Relevance
“…This might be connected to differences in sensitivity between fungi and plants. Our finding is in line with the less known role of antibiotics in the environment; they are important signaling molecules and therefore widespread in natural habitats with high microbial diversity [ 51 ]. Former studies showed mainly direct antibiosis for Streptomyces –fungi interactions [ 52 ].…”
Section: Discussionsupporting
confidence: 87%
“…This might be connected to differences in sensitivity between fungi and plants. Our finding is in line with the less known role of antibiotics in the environment; they are important signaling molecules and therefore widespread in natural habitats with high microbial diversity [ 51 ]. Former studies showed mainly direct antibiosis for Streptomyces –fungi interactions [ 52 ].…”
Section: Discussionsupporting
confidence: 87%
“…However, the same mechanisms can also serve as an essential feature of nosocomial pathogens to overcome high (toxic) antimicrobial concentrations that are found in clinical settings [59,61]. The high diversity of ARGs that was detected in the present study, reflects the natural complexity of microbial communities that are commonly associated with lichens, and have previously been shown to provide metabolic versatility that facilitates plasticity of the lichen holobiont [13,62].…”
Section: Discussionsupporting
confidence: 54%
“…Our data highlights that the natural microbiome of Peltigera comprises highly diverse and low abundant intrinsic ARGs, which provide a retrievable basis to cope with antimicrobial pressure. Similar to other relatively pristine environments, ARGs were found to be ubiquitous and to harbour a high number of different efflux pump systems [13,59,60]. In nature, ARGs fulfil various roles and are commonly involved in processes such as detoxification and molecular signalling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria are known to be the main constituent of the bog microbiome, co-occurring and interacting with archaea, fungi and other members of the microbiome [ 8 , 12 , 13 ]. Moreover, bog ecosystems were found to be natural hotspots for a high diversity of bacterial species and antagonists [ 12 ] and microbial genes [ 11 ] and interestingly also for antibiotic resistance genes [ 4 , 11 , 14 ]. A vast majority of bog bacteria were found to engage in a plant-associated, often endophytic life style [ 4 ].…”
Section: Introductionmentioning
confidence: 99%